Effect of Shockwave Therapy on Low Back Pain in Primary Dysmenorrhea - Anter Ahmed, Anan Abd El Shafey; Ahmed Awad, Mohamed; Botla, Afaf M.; AbdelWahab Mahmoud, AbdelRahman Hegazy; Ahmed Hussein, Ahmed Aref (Journal of Neonatal Surgery, 2025)
Purpose: This study was conducted to explore shockwave therapy's efficacy in managing low back pain (LBP) associated with primary dysmenorrhea (PD). Subjects: Sixty patients complaining of LBP during PD participated in this study. Participants' ages ranged from 18 to 30 years, and all subjects presented with body mass indices not exceeding 29 kg/m2. Design: A randomized controlled methodology was employed for this study. They were divided into two equal groups: Group A, which was treated with hot packs for three consecutive menstrual cycles. Group B which was treated with hot packs in addition to shockwave therapy for three consecutive menstrual cycles. Assessment: LBP intensity was evaluated using a visual analogue scale (VAS) and pressure algometer (PA) measurements for all participants in Groups A and B before intervention and following each of three consecutive menstrual cycles. The Oswestry disability index (ODI) was employed to assess pain-related functional limitations before and after the intervention protocol. Results: Statistical analysis revealed significant within-group improvements in both groups, demonstrated by decreased VAS scores, increased PA values, and reduced ODI measurements following intervention. The between-group comparison demonstrated significant differences across all outcome measures, with Group B achieving superior therapeutic outcomes characterized by greater pain reduction, higher pain thresholds, and enhanced functional improvement. Conclusion: Shockwave therapy is an effective adjunctive intervention for managing LBP in PD through reducing VAS scores, increasing PA measurements, and decreasing ODI values.